A Novel Insight into the Anti-Urolithiatic Effect of Manjistha and Triphala Syrup Formulation - Pokharkar, Deepak; Elangovan, Suchitra; Dabhade, Trupti; Kamble, Mitali; Pokharkar, Aditi (Journal of Neonatal Surgery, 2025)
Urolithiasis is a common, painful renal disorder of calcium oxalate crystal precipitation. Some traditional medicines have been found to have anti-urolithiatic actions, including Manjistha (Rubia cordifolia) and Triphala. This study investigates the litholytic potential of a polyherbal syrup made from these plants. Hydroalcoholic extracts of R. cordifolia roots and Triphala were prepared by Soxhlet extraction. The herbal syrup was then subjected to anti-urolithiatic testing in vitro, through methodologies such as egg membrane assay and sedimentary crystal formation model. Cystone was taken as a reference standard. TLC was adopted for phytochemical profiling of the extracts. TLC helped identify the main phytoconstituents such as gallic and ellagic acids. Using the egg membrane assay method, the dissolution of calcium oxalate crystals was found to be 48% by the herbal syrup, while for Cystone this value was 54%. The sedimentary crystal model revealed a significant reduction in calcium oxalate crystals under treatment as compared with the control. The preparation showed promising effects of anti-urolithiatic activity in vitro, which could be due to synergistic phytoconstituent effects. These findings support its traditional usage and its potential for the natural treatment of urolithiasis. It is further suggested that investigating the activity in vivo, followed by clinical experiments, would be recommended for its confirmation.